The Effect Of The Combination Of Benson Relaxation Technique And Lemon Aromatherapy On Labor Pain During The Active Phase At The Regional General Hospital Subulussalam City - Ayu Jani Puspita Sari; Ramaita Souraya Kombih (Sean Institute, 2023)
All labor processes can cause a discomfort response in the form of pain. A non-pharmacological way that can help reduce pain is to provide a combination of benson relaxation and lemon aromatherapy. The problem of this study is whether there is an effect of a combination of benson relaxation techniques and lemon aromatherapy on labor pain in the first phase of active labor. The purpose of the study was to analyze the effect of a combination of benson relaxation techniques and lemon aromatherapy on labor pain in the first phase of active labor. This research is a quasi experiment with pre test and posttest design with control group design. The study population was 150 people and a sample of 15 people in the control group and 15 people in the intervention group. Samples were taken with systematic random sampling technique. The research location was in the delivery room of Subulussalam City Hospital. The control group was intervened according to the hospital SOP and the intervention group was given a combination of benson relaxation and lemon aromatherapy. Data analysis using t test with the results there was no difference in mean pain intensity before (7.72) and after (7.40) treatment in the control group with a p value = 0.0317>0.05. In the intervention group, there was a significant difference in average pain intensity before (7.20) with after (5.87) given a combination of benson relaxation and lemon aroma therapy with a p value of 0.05. The combination technique of benson relaxation and lemon aromatherapy is a nonpharmacological therapy that can improve the response to adaptation of labor pain in the active phase I so that pain can be reduced.